2011
DOI: 10.1186/1687-1499-2011-59
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive antenna selection and Tx/Rx beamforming for large-scale MIMO systems in 60 GHz channels

Abstract: We consider a large-scale MIMO system operating in the 60 GHz band employing beamforming for high-speed data transmission. We assume that the number of RF chains is smaller than the number of antennas, which motivates the use of antenna selection to exploit the beamforming gain afforded by the large-scale antenna array. However, the system constraint that at the receiver, only a linear combination of the receive antenna outputs is available, which together with the large dimension of the MIMO system makes it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…However, to the best of our knowledge, there are only few studies on antenna selection for massive MIMO available. In [43], antenna selection in massive MIMO was addressed for short-range wireless communications at 60 GHz. In [44], a simulation study using the Kronecker channel model [45] showed that significantly higher performance can be achieved with antenna selection than without.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are only few studies on antenna selection for massive MIMO available. In [43], antenna selection in massive MIMO was addressed for short-range wireless communications at 60 GHz. In [44], a simulation study using the Kronecker channel model [45] showed that significantly higher performance can be achieved with antenna selection than without.…”
Section: Introductionmentioning
confidence: 99%
“…Selection methods for reducing the complexity of massive MU-MIMO systems is a widely explored field [8], [12]- [14]. There are many works related to antenna selection in LOS channels, see e.g., [15], [16]. The optimal selection of antennas is very complicated.…”
Section: Ergodic Beamformingmentioning
confidence: 99%
“…whereh q,p (ω) is the flat-fading CIR defined in (9) and v (m) q refers to the noise with zero mean and power density N 0 .…”
Section: B Sequential Stochastic Approximation (Ssa)mentioning
confidence: 99%
“…Searching in brute force is simple and effective for single link, but it is impractical in our case because the total search space spanned by Q systems is extremely large even the multistage strategy is used. To improve the search efficiency, we resort to the stochastic approximation (SA) algorithm, which originated in operation research [8] and applied in MIMO antenna selection [9] and sensor network encoding [10].…”
Section: Problem Formulationmentioning
confidence: 99%